कतिपय राष्ट्रव्यापी समस्याओं के समाधान में वैदिक धर्म की चिन्तन दृष्टि - Shikha .; Reena Bajpayee (Dr. Chinmay Pandya, 2012)
संवेदना को परिष्कृत करने वाली विधा का नाम धर्म है। वैदिक साहित्य के अनुसार मनुष्य जीवन को सफल तथा समाज को सभ्य एवं सुसंस्कृत बनाने की जो सर्वोच्च आचार संहिता है उसे धर्म के नाम से जाना जाता है। धर्मवेत्ता वह है जो सर्वश्रेष्ठ मानवीय गुणों से सुसंपन्न है तथा समस्त मानव जाति को एक परमात्मा की संतान मानता है। जो तत्व प्राणियों द्वारा धारण किया जाता है तथा इसके द्वारा वह प्राणियों का पालन-पोषण करता हुआ उन्हें सुख-शांति से आप्यायित करता है व अवलंबन देता है उसे धर्म कहते हैं। इस प्रकार सारी विश्व मानवता के लिए धर्म एक ही हुआ, जिसके मार्गदर्शन, संरक्षण में जिसकी छाया तले सभी प्रकार की विचारधारायें समान रूप से पोषण पाती रहें, पारस्परिक कोई विग्रह न हो, वह धर्म शाश्वत है व एक ही है। देवसंस्कृति इस संबंध में हमारा मार्गदर्शन आज की साम्प्रदायिक विद्वेष भरी परिस्थितियों में समुचित रीति-नीति से करती हुई कहती है कि वही धर्म कहलाने योग्य है जो सहिष्णु हो, जिसकी मर्यादा-अनुशासन का अवलम्बन सब लें, जो नीतिमत्ता पर आधारित हो तथा जो सबको समान संरक्षण प्रदान करती हो। परंतु आज धर्म का यह वास्तविक स्वरूप विलुप्त हो गया है, धर्म मात्र कर्मकाण्ड बनकर रह गया है। धर्म के नाम पर सर्वत्र अंधविश्वास फैला हुआ है। धर्म के वास्तविक स्वरूप से दूर होने के कारण आज समाज में अनेक समस्याएंँ उत्पन्न हो गयी हैं। धार्मिक कट्टरता के कारण साम्प्रदायिकता ने जन्म लिया है। इसके अतिरिक्त जातिवाद, क्षेत्रवाद जैसी समस्याएँ समाज को विकृत करती चली जा रही हैं। आतंकवाद का दंश तो भारत ही नहीं संपूर्ण विश्व झेलने के लिए विवश है।  इन समस्याओं के समाधान में वैदिक धर्म की महती भूमिका है। यदि मानव मात्र धर्म के वास्तविक स्वरूप (वैदिक धर्म) को अपने जीवन में अंगीकार कर ले तो उपरोक्त समस्याओं से निजात पा सकना संभव है। वैदिक ग्रंथों में धार्मिक सद्भाव एवं धार्मिक सामंजस्य का उल्लेख प्राप्त होता है। धार्मिक सद्भाव का तात्पर्य है अन्य धर्म सम्प्रदायों को भी अपने धर्म के समान आदर व प्रेम की भावना को प्रश्रय देना। इस भावना के अवलंबन में सम्प्रदायवाद की समस्या का समाधान निहित है। धार्मिक सामंजस्य का तात्पर्य है व्यक्ति व व्यक्ति के मध्य संकीर्ण, स्वार्थपरक मनोवृत्तियों व मनोभावों के स्थान पर ''आत्मवत् सर्वभूतेषु'' व ''वसुधैव कुटुम्बकम' की भावना का विकास अर्थात् जब एक मनुष्य दूसरे मनुष्य को अपने समान और संपूर्ण वसुधा को अपने परिवार के समान समझेगा तो समस्त प्रकार के विद्वेष स्वतः ही समाप्त हो जायेंगे परिणामतः जातिवाद, क्षेत्रवाद, आतंकवाद जैसी समस्याओं का निर्मूलन संभव हो सकेगा। इस प्रकार वैदिक धर्म सामाजिक समस्याओं के समाधान में महत्वपूर्ण भूमिका का निर्वाह कर सकता है। Dharma is the mode to sophisticated sympathy. According to Vedic literature, Dharma is the supreme code of conduct to make a person's life successful, develop civilized and well cultured society. The preacher is the one who is endowed of the best human qualities and considers the entire human race as the child of a divine God. The quality-element which is lived by the living being and through it, it nurtures all living beings and gives them peace and support is called Dharma. Thus, Dharma is the same for the whole humanity, under whose guidance, under whose shadow all kinds of ideologies are nourished equally, and there should be no mutual dissidence, this religion (Dharma) is eternal and the same. In this regard devic culture guides us in current Communal malice with appropriate custom by stating that it is worthy to be called dharma only, if it has quality of patience, whose dignity and discipline can be sustentation and provides equi protection to all. But today this true form of Dharma has become extinct, religion has become a mere ritual. Superstition is spread everywhere in the name of religion Dharma. Today many problems have arisen in society due to being unaware of the true nature of religion ( Dharma). Due to religious fanaticism, communalism is born. Apart from this, problems like casteism and regionalism continue to distort the society. Not only India, the world is facing the brunt of terrorism.Vedic religion has an important role in solving these problems. If human beings adopt the true nature of religion (Vedic religion) in their lives, then it is possible to get rid of the above problems. Religious amiableness  and religious harmony are mentioned in Vedic texts. Religious amiableness means promoting the spirit of respecting and loving  other religious communities as well as their religion. The solution to the problem of communalism lies in the adherence to this feeling of religious amiableness. Religious harmony refers to the development of a sense of "(aatmavat sarvabhuteshu), one should feel happiness and distress of others as his own" and "(vasudhaiv kutumbakam), the world is one family." in the place of narrow minded, selfish attitudes and feelings between the individual and the person, ie when one human thinks  another man as his own and their family as his own family.